SPE Annual Technical Conference and Exhibition 2012
DOI: 10.2118/155499-ms
|View full text |Cite
|
Sign up to set email alerts
|

PVT in Liquid-Rich Shale Reservoirs

Abstract: This paper addresses sampling and PVT modeling of liquid-rich fluids produced from ultra-tight formations – "liquid-rich shale" (LRS) reservoirs.1 Proper PVT treatment in these unconventional reservoirs is important to provide improved short- and long-term oil and gas production forecasts, and define the initial oil and gas in place. We give recommended practices for sampling, laboratory PVT tests, developing PVT (EOS and black-oil) models, and estimating the in-situ reservoir fluid system (comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(42 citation statements)
references
References 5 publications
2
40
0
Order By: Relevance
“…This observation is consistent with the findings of Whitson and Sunjerga (2012) and with our mathematical derivations for the linear flow regime. Based on numerical simulations, Whitson and Sunjerga (2012) found that the liquid yield (r p ¼ 1/GOR) remains approximately constant for long periods of constant FBHP in LRS reservoirs. They noted this behavior to be characteristic of LRS reservoirs for the case of infinite-acting flow, when the flow is 1D planar.…”
Section: Pseudopressure Calculation and Saturationepressure Relationshipsupporting
confidence: 93%
“…This observation is consistent with the findings of Whitson and Sunjerga (2012) and with our mathematical derivations for the linear flow regime. Based on numerical simulations, Whitson and Sunjerga (2012) found that the liquid yield (r p ¼ 1/GOR) remains approximately constant for long periods of constant FBHP in LRS reservoirs. They noted this behavior to be characteristic of LRS reservoirs for the case of infinite-acting flow, when the flow is 1D planar.…”
Section: Pseudopressure Calculation and Saturationepressure Relationshipsupporting
confidence: 93%
“…They concluded that thermodynamic properties, fluid phase behavior, and IFT between the fluid and pore surface are altered in the nanoporous media. Zarragoicoechea and Kuz (2004) modeled the reduction of critical temperature applying the van der Waals model and reported a good match of their model and the experimental data by Morishige et al (1997). The Zarragoicechea and Kuz (2004) model relates the relative critical-temperature shift quadratically to the ratio of the LJ collision diameter to the pore-throat radius, r LJ =r p (Eq.…”
Section: Critical-properties Shift In Confined Spacementioning
confidence: 97%
“…Similarly, Devegowda et al (2012) point out that interactions between molecules and between molecules and pore surface alter the fluid properties because the pore surface available per unit volume increases as the pore size decreases. Zarragoicoechea and Kuz (2004) illustrated that the critical properties of the components should be shifted as a function of the ratio of the molecular size to the pore size. Travalloni et al (2010) state that, as pore size becomes smaller (typically, for pore-to-molecule size less than 20), the thermo-physical and dynamic properties of confined fluids could deviate significantly from the ones measured in the pressure/volume/temperature (PVT) cell.…”
Section: Confined-space Phase Behaviormentioning
confidence: 99%
“…The work of Whitson and Sunjerga (2012) showed that the depletion behaviors of tight reservoirs depend greatly on reservoir permeability; therefore, the production decline will be impacted by reservoir permeability dynamics during the depletion process. At the very early stage of well production, the entire reservoir is not affected by the depletion and the reservoir energy is at maximum.…”
Section: Figure 1-overlay Of Gas Production Rate From Various Tight Smentioning
confidence: 99%